β1 Integrin Regulates PC3 Prostate Cancer Cell Phenotypes in part via Regulation of Matricellular SPARC - Bugiel, Steven (Université d'Ottawa / University of Ottawa, 2016)
We have shown herein that β1 integrin stably depleted PC3 sub-clonal cells confer a trend towards increased survival of mice compared to β1 integrin expressing counterparts when tested in an intracardial bone metastasis model. Therefore, we sought to investigate novel factors that mediate β1 integrin-dependent cellular migration and three dimensional growth of prostate cancer PC3 cells in vitro. We show herein that depletion of β1 integrin using siRNA directed techniques results in increased SPARC protein expression. We further show that suppression of SPARC by β1 integrin appears to occur through a JNK dependent mechanism. Moreover, siRNA mediated depletion of β1 integrin results in impaired sphere formation in 3D BME assays. This was mediated in part by the increased production of SPARC. β1 integrin-depleted cells also diminished the enhanced migration of cells on the predominant bone matrix, collagen I. Concomitant SPARC depletion in β1 integrin-depleted cells did not rescue this enhanced migration. These findings suggests that the role of β1 integrin in mediating 3D growth of PC3 cells occurs at least in part through the suppression of SPARC protein expression.
Keywords: Prostate Cancer; Metastasis; Integrins; Extracellular Matrix; SPARC